3D printing inorganic bone cement bone tissue engineering scaffold and preparation method thereof
Patent Information
- Application Number
- CN202311677414.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-08
AI Technical Summary
克服现有技术中无机骨水泥浆料直接3D打印成型出现滤压、相分离、堵塞等问题,避免了为提高无机骨水泥浆体3D打印性能增加打印辅助装置
[0024]1.本发明是将无机骨水泥浆体注入到3D打印成型的热塑性高分子模具中成型,并通过两步热处理的方式彻底清除热塑性高分子,最终得到无机骨水泥骨组织工程支架,可以有效的控制支架的孔结构,如孔尺寸、孔形状、孔的连通性等,克服了无机骨水泥直接打印成支架的难点和缺点,设备投入少,制备流程简单,易操作,可靠性强。通过调控内模具的结构参数,可以对无机骨水泥骨组织工程支架的孔道结构进行个性化定制。
Smart Images

Figure CN117582543B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of 3D printed bone repair materials, and more specifically to a 3D printed assisted construction of bone cement bone tissue engineering scaffold. Background Technology
[0002] The information disclosed in the background section of this invention is intended only to enhance the understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] 3D printing has been widely applied in orthopedics, such as printing preoperative lesion models, personalized prostheses and implants, external fixation braces, and tissue engineering scaffolds. This can meet the needs of specific diseases and patients, reduce the cost of bone repair treatment, and improve treatment success rates. Inorganic bone cement (such as calcium phosphate bone cement and calcium silicate bone cement) has been widely used clinically due to its excellent self-curing properties, malleability, biocompatibility, and osteoinductive (or osteostimulatory) properties. Because inorganic bone cement slurry has rheological properties, it can be extruded from a 3D printing nozzle and stacked to form a three-dimensional component after curing, thus enabling 3D printing. However, inorganic bone cement slurry is a non-Newtonian fluid, belonging to the category of plastic fluids. When the shear force of the flow varies within a small range, the fluid material generally does not flow; flow only occurs when a certain value is reached. Therefore, direct 3D printing of inorganic bone cement, i.e., printing a structure equal to the final model, requires the development of devices and equipment that facilitate the printing of inorganic bone cement. For example, to prevent phase separation and clogging problems in inorganic bone cement slurry during 3D printing, a piezoelectric contactor was invented (authorization announcement number: CN112720779B). However, direct 3D printing of inorganic bone cement slurry also suffers from drawbacks such as low printing accuracy, poor interlayer adhesion, and limited controllability of the pore structure of the printed bone tissue engineering scaffold, as well as a small adjustable pore size range.
[0004] To address the problems associated with directly 3D printing inorganic bone cement to construct bone tissue engineering scaffolds, 3D printing-assisted construction of these scaffolds can be employed. Chinese Patent CN 108478879 A discloses a porous calcium phosphate / natural polymer composite scaffold, its preparation method, and its application. This method uses a large amount of organic solvent (such as dichloromethane) to dissolve and remove the mold used in the 3D printing process, resulting in a porous calcium phosphate / natural polymer composite scaffold. However, the organic solvent dissolution process easily causes swelling, damaging the composite scaffold structure and leading to structural failure. The organic solvent also dissolves the natural polymer, further damaging the scaffold structure. Furthermore, the toxicity of the organic solvent and its residues result in poor biocompatibility of the bone tissue engineering scaffold, failing to meet clinical needs. Chinese Patent CN113233887A discloses a controllable porous calcium phosphate scaffold and its preparation method, which uses high-temperature sintering to remove the auxiliary organic scaffold, obtaining a calcium phosphate ceramic scaffold. However, calcination causes uncontrollable shrinkage, resulting in extremely poor dimensional and internal dimensional stability, making it difficult to meet personalized requirements. Incomplete combustion of the organic scaffold during calcination causes carbonization and other problems, making it difficult to degrade after implantation. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a 3D-printed inorganic bone cement bone tissue engineering scaffold and its preparation method. This method is suitable for various bone cements such as calcium phosphate, calcium silicate, and magnesium phosphate. The equipment is simple, the operation is convenient, and the cost is low, without the use of any organic solvents. The internal pore structure and shape of the constructed inorganic bone cement bone tissue engineering scaffold can be customized, achieving a design-to-result ratio. The internal pore structure is interconnected, resulting in high structural strength, which is beneficial for cell and tissue growth. This invention overcomes the problems of filtration, phase separation, and clogging that occur when directly 3D printing inorganic bone cement slurry in existing technologies, and avoids the need for additional printing auxiliary devices to improve the 3D printing performance of inorganic bone cement slurry. The preparation process of this method is simple, reliable, and efficient. Precise control of the pore structure and shape can be achieved to meet personalized needs, improving the mechanical properties and precision of the inorganic bone cement bone tissue engineering scaffold while reducing its construction cost. The inorganic bone cement bone tissue engineering scaffold of this invention uses simple materials and is non-cytotoxic. This invention overcomes the disadvantages of direct 3D printing of inorganic bone cement due to the layer-by-layer printing process, and possesses a controllable shape and internal porous structure. The invention thoroughly removes thermoplastic polymers through a two-step heat treatment process, avoiding problems such as dissolution and expansion, direct decomposition and expansion leading to scaffold structure damage, and also avoiding the problem of carbonization during high-temperature calcination. The bone tissue engineering scaffold constructed by this invention undergoes hydrothermal high-temperature and high-pressure treatment to sterilize it, making it suitable for direct clinical use or preservation, and convenient to use.
[0006] To achieve the above objectives, the present invention employs the following technical solution: a method for preparing a 3D-printed inorganic bone cement bone tissue engineering scaffold, comprising the following steps:
[0007] (1) On a fused deposition modeling 3D printer platform, using thermoplastic polymer materials as raw materials, print the inner and outer molds of inorganic bone cement bone tissue engineering scaffolds;
[0008] (2) The mixing liquid is mixed with inorganic bone cement powder to form a uniform inorganic bone cement slurry, which is then injected into a bone tissue engineering scaffold mold for curing.
[0009] (3) After curing, first remove the outer mold, and then use the hot melt method to initially remove the inner mold;
[0010] (4) Then use the hydrothermal method to thoroughly remove the remaining inner mold;
[0011] (5) After removal, clean and dry to obtain a 3D printed inorganic bone cement bone tissue engineering scaffold.
[0012] A 3D-printed inorganic bone cement bone tissue engineering scaffold and its preparation method are disclosed. First, an inner and outer mold for the inorganic bone cement bone tissue engineering scaffold are designed according to requirements. Then, using thermoplastic polymer materials as raw materials, the inner and outer molds of the inorganic bone cement bone tissue engineering scaffold are printed on a fused deposition modeling (FDM) 3D printer platform. A mixing liquid and inorganic bone cement powder are mixed at a liquid / solid ratio of 0.25–0.60 mL / g to form a homogeneous inorganic bone cement slurry. This slurry is injected into the bone tissue engineering scaffold mold and rapidly cured at 40–80°C. After curing for 1.0–6.0 hours, the outer mold is removed first, and then the scaffold is placed in a furnace at 150–200°C and held for 0.5–4.0 hours to preliminarily remove the inner mold. Finally, the inorganic bone cement bone tissue engineering scaffold with the inner mold preliminarily removed is placed in a hydrothermal reactor and reacted at 140–220°C for 1.0–8.0 hours to completely remove the inner mold. After removal, the scaffold is cleaned and dried at 40–80°C for 1.0–4.0 hours to obtain a 3D-printed inorganic bone cement bone tissue engineering scaffold. The gap inside the scaffold is greater than 0.2 mm, and the width of the inner column of the inorganic cement bone tissue engineering scaffold is not less than 0.5 mm.
[0013] Furthermore, the thermoplastic polymer material is one or any combination of polylactic acid (PLA), polyethylene (PE), polyvinyl alcohol (PVA), etc.
[0014] Furthermore, inorganic bone cement is classified into one or any combination of calcium phosphate bone cement, calcium silicate bone cement, and magnesium phosphate bone cement; inorganic bone cement consists of powder and curing liquid; the inorganic bone cement powder is one or any combination of tricalcium phosphate, tetracalcium phosphate, amorphous calcium phosphate, trimagnesium phosphate, magnesium hydrogen phosphate, magnesium oxide, tricalcium silicate, dicalcium silicate, and alkaline activated nano-silica self-curing powder; the mixing liquid is one or any combination of water, sodium chloride aqueous solution, calcium chloride aqueous solution, and magnesium chloride aqueous solution; the liquid / solid ratio is 0.25–0.60 mL / g.
[0015] Furthermore, the inorganic bone cement bone tissue engineering scaffold mold is divided into an inner mold and an outer mold. The inner mold is the internal channel structure of the inorganic bone cement bone tissue engineering scaffold, and the outer mold is the external model of the inorganic bone cement bone tissue engineering scaffold, and is provided with an injection port for bone cement slurry.
[0016] Preferably, the support mold is constructed on a fused deposition modeling (FDM) 3D printer platform.
[0017] Preferably, the thermoplastic polymer material also has the properties of low melting point and good biocompatibility.
[0018] Preferably, the inorganic bone cement is calcium phosphate bone cement or calcium silicate bone cement, and the mixing liquid is water.
[0019] Further, the inner mold is initially removed by placing it in a furnace at 150-200℃ and holding it for 0.5-4.0 hours.
[0020] Furthermore, thoroughly clean the inner mold and place it in a hydrothermal reactor, maintaining it at 140–220°C for 1.0–8.0 hours.
[0021] Preferably, the thermoplastic polymer is removed in two steps: first, the inner mold is removed by heating, and then the inner mold is completely removed by hydrothermal method.
[0022] Using the above technical solution, the gap inside the 3D printed inorganic bone cement bone tissue engineering scaffold is greater than 0.2mm, and the width of the inner column of the inorganic bone cement bone tissue engineering scaffold is not less than 0.5mm.
[0023] The beneficial effects obtained by this invention are as follows:
[0024] 1. This invention involves injecting inorganic bone cement slurry into a 3D-printed thermoplastic polymer mold, followed by a two-step heat treatment process to completely remove the thermoplastic polymer, ultimately yielding an inorganic bone cement bone tissue engineering scaffold. This method effectively controls the pore structure of the scaffold, such as pore size, shape, and connectivity, overcoming the difficulties and drawbacks of directly printing inorganic bone cement into scaffolds. It requires less equipment investment, has a simple and easy-to-operate preparation process, and high reliability. By adjusting the structural parameters of the inner mold, the pore structure of the inorganic bone cement bone tissue engineering scaffold can be customized.
[0025] 2. This invention thoroughly removes thermoplastic polymers through a two-step heat treatment process, avoiding problems such as dissolution and expansion, and direct decomposition and expansion of thermoplastic polymers that could lead to scaffold structure damage. It also avoids the problem of carbonization during high-temperature calcination. Compared to the high-temperature calcination method for removing the mold to obtain calcium phosphate ceramic scaffolds, the scaffold constructed by this method exhibits no shrinkage behavior, stable shape and internal dimensions, and is directly derived from the design. Furthermore, the final product of the scaffold prepared using calcium phosphate bone cement is hydroxyapatite [Ca]. 10 [(PO4)6(OH)2] has the same main inorganic components as bone, and thus has better biocompatibility.
[0026] 3. The method of the present invention is simple to operate and fast, and can prepare inorganic bone cement bone tissue engineering scaffolds of different types and compositions, such as calcium phosphate bone cement, calcium silicate bone cement, magnesium phosphate bone cement, and inorganic bone cement composed of various powders such as calcium phosphate, calcium silicate, and calcium phosphate.
[0027] 4. The scaffold constructed by this invention has a variety of controllable pore structures, which is beneficial for the exchange of substances between the scaffold and bone tissue and the ingrowth of blood vessels and bone tissue after implantation.
[0028] 5. The bone tissue engineering scaffold structure constructed by this invention has stable mechanical properties and can be designed with different mechanical structures.
[0029] 6. The bone tissue engineering scaffold constructed by this invention undergoes high-temperature and high-pressure hydrothermal treatment to sterilize it, making it suitable for direct clinical use or preservation, and convenient to use.
[0030] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, the following describes the preferred embodiment in detail with reference to the accompanying drawings. Attached Figure Description
[0031] Figure 1 Micro CT images of inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffolds and internal molds.
[0032] Figure 2Micro CT images of inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffolds (a. stereoscopic view; b. X-Y section; c. Y-Z section; d. Z-X section)
[0033] Figure 3 Images of inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffolds (a. 3D view; b. top view; c. side view)
[0034] Figure 4 Images of inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffolds (a. 3D view; b. top view; c. side view)
[0035] Figure 5 SEM images of the interior of the inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold during the processing (a. curing at 80℃ for 5.0 hours, b. holding at 180℃ for 2.0 hours, c. hydrothermal treatment at 180℃ for 4.0 hours).
[0036] Figure 6 Images of a cylindrical inorganic bone cement (calcium silicate bone cement) scaffold for bone tissue engineering (a. 3D view; b. top view; c. side view).
[0037] Figure 7 Image of a non-standard inorganic bone cement scaffold for bone tissue engineering (a. actual object) Figure 1 b. physical objects Figure 1 c. Physical objects Figure 1 Top surface; d. physical object Figure 1 (Top surface)
[0038] Figure 8 Morphological photographs of bone tissue engineered with inorganic bone cement (calcium phosphate bone cement) 3 weeks (a) and 6 weeks (b) after implantation. Detailed Implementation Plan
[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0040] Example 1:
[0041] Using polylactic acid (PLA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) 3D printer (such as Creality Ender-5s). The outer mold dimensions were 20×20×30mm, the inner mold gap was 1.5×1.5×1.5mm, and the filament width was 1.0mm. Tricalcium phosphate and tetracalcium phosphate were selected as inorganic bone cement (calcium phosphate bone cement) powders, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.40ml / g and injected into the 3D printing mold. After curing at 80℃ for 1.0 hour, it was placed in an oven at 180℃ and held for 1.0 hour. Then, it was placed in a hydrothermal reactor and held at 140℃ for 2.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold.
[0042] During the process, after the inorganic bone cement was injected into the 3D printed mold and cured, MicroCT scanning analysis was performed, and the results are as follows: Figure 1 As shown, the flowability of the inorganic bone cement (white) ensures that it can effectively fill the gap (1.5×1.5×1.5mm) in the inner mold. The inner mold is the channel structure of the inorganic bone cement bone tissue engineering scaffold, and the channel width is the wire width of the inner mold (1.0mm).
[0043] Due to the close fit between the bone cement and the inner mold ( Figure 1 If a solvent (such as acetone) is used to dissolve and remove the inner mold during implementation, the polymer in the inner mold will expand rapidly after absorbing the solvent, leading to structural damage.
[0044] If the inner mold is removed by direct high-temperature calcination, the incomplete combustion of the polymer in the inner mold will easily cause carbon deposition, the size of the support will shrink significantly, and internal stress will also be generated.
[0045] If the inner mold is removed directly using the hydrothermal method, the polymer in the inner mold will rapidly decompose thermally, expand in volume, and damage its structure, leading to structural collapse. Therefore, this invention innovatively employs a more effective two-step method (thermal melting and hydrothermal method) to remove the inner mold (thermoplastic polymer) in stages.
[0046] Example 2:
[0047] Using polyethylene (PE) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) 3D printer (such as the A6). The outer mold dimensions were 5×15×20mm, the inner mold gap was 1.5×1.5×1.5mm, and the filament width was 1.0mm. Tricalcium phosphate and tetracalcium phosphate were selected as inorganic bone cement (calcium phosphate bone cement) powders, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.35ml / g and injected into the 3D printing mold. After curing at 80℃ for 2.0 hours, it was placed in an oven at 180℃ and held for 2.0 hours. Then, it was placed in a hydrothermal reactor and held at 140℃ for 6.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold. During the process, after curing at 80℃ for 2.0 hours, the material was placed in a 180℃ furnace and held for 2.0 hours, a process known as hot-melt treatment. The thermoplastic polymers flowed naturally out of the bone cement scaffold, but some thermoplastic polymers remained inside the scaffold. The material was then placed in a hydrothermal reactor and held at 140℃ for 6.0 hours, a process known as hydrothermal treatment. Under high temperature and pressure, the remaining thermoplastic polymers (polyethylene, PE) were completely removed, separating into water and carbon dioxide.
[0048] During the process, MicroCT scanning analysis was performed on the inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold, and the results are as follows: Figure 2 As shown, Figure 2 'a' is a 3D stereoscopic image. Figure 2 b, c, and d are cross-sectional views in three directions. The thermoplastic polymer removal process is non-toxic and residue-free, and can be completely removed. The inorganic bone cement bone tissue engineering scaffold maintains a pore width equal to the wire width of the inner mold (1.0 mm). The structural columns and pore structures of the inorganic bone cement bone tissue engineering scaffold are respectively the pores and structure of the mold. Compared with the calcium phosphate ceramic scaffold obtained by removing the mold using high-temperature calcination, the scaffold constructed by this method exhibits no shrinkage behavior, stable shape and internal dimensions, and is exactly what is designed. Furthermore, the final product of the scaffold prepared using calcium phosphate bone cement is hydroxyapatite [Ca]. 10 [(PO4)6(OH)2] has the same main inorganic components as bone, and thus has better biocompatibility.
[0049] Because the bone cement and the inner mold fit together tightly (e.g. Figure 1As shown in the diagram, if the material is cured at 80℃ for 2.0 hours, it is then placed in a hydrothermal reactor and kept at 140℃ for 6.0 hours, i.e., treated first using the hydrothermal method. Because thermoplastic polymers decompose into water and carbon dioxide under high temperature and pressure, and the bone cement and inner mold in the system are tightly bonded with no space, expansion will destroy the structure of the scaffold, resulting in an incomplete scaffold. This indicates that the steps in this method require strict adherence to operating procedures. The innovative two-step method (thermal melting and hydrothermal methods) of this invention to remove the inner mold (thermoplastic polymer) in stages is more effective.
[0050] Example 3:
[0051] Using polyethylene (PE) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) 3D printer. The outer mold dimensions were 12×14×22mm, the inner mold gap was 1.5×1.5×1.5mm, and the filament width was 1.0mm. Tricalcium phosphate and tetracalcium phosphate were selected as inorganic bone cement (calcium phosphate bone cement) powders, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.40ml / g and injected into the 3D printing mold. After curing at 60℃ for 3.0 hours, it was placed in a 190℃ furnace and held for 1.0 hour. Then, it was placed in a hydrothermal reactor and held at 180℃ for 4.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold.
[0052] Actual photos of the object are as follows Figure 3 As shown, the inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold structure is complete, with a clear internal structure and stable structural dimensions. Figure 3 Image c also shows the layered structure during the thermoplastic polymer 3D printing process. Combined with Examples 1 and 2, it demonstrates that the dimensions of the inorganic bone cement bone tissue engineering scaffold are controllable. In direct 3D printing of bone cement scaffolds, the cement curing between layers occurs sequentially, resulting in distinct interfaces between layers, weak interlayer adhesion, and fractures often occurring between layers. The inorganic bone cement bone tissue engineering scaffold constructed using this method is integrally formed, without interlayer interfaces, and exhibits strong mechanical stability.
[0053] Example 4:
[0054] Using polylactic acid (PLA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) printer. The outer mold dimensions were 12×20×27mm, the inner mold gap was 1.8×1.8×1.8mm, and the filament width was 0.7mm. Tricalcium silicate was selected as the inorganic bone cement (calcium silicate bone cement) powder, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.30ml / g and injected into the 3D printing mold. After curing at 80℃ for 5.0 hours, it was placed in a 190℃ furnace and held for 1.0 hour. Then, it was placed in a hydrothermal reactor and held at 200℃ for 4.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold.
[0055] Actual photos of the object are as follows Figure 4 As shown, the inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold has a complete structure, clear internal structure, and stable structural dimensions. It is constructed from bone cement structural columns with a cross-section of 1.8×1.8mm, and the width of the internal channels is the wire width of the inner mold, reduced to 0.7mm. Figure 4 The layered structure of thermoplastic polymers during 3D printing can also be seen in image c.
[0056] Combined with Examples 1, 2 and 3, it is shown that the external dimensions and internal pores of the inorganic bone cement bone tissue engineering scaffold are controllable. This method is also applicable to various types of inorganic bone cement, such as calcium phosphate bone cement and calcium silicate bone cement.
[0057] Example 5:
[0058] Using polylactic acid (PLA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) printer. The outer mold dimensions were 30×30×40mm, the inner mold gap was 1.8×1.8×1.8mm, and the filament width was 0.7mm. Tricalcium silicate was selected as the inorganic bone cement (calcium silicate bone cement) powder, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.40ml / g and injected into the 3D printing mold. After curing at 80℃ for 5.0 hours, it was placed in a 180℃ oven and held for 2.0 hours. Then, it was placed in a hydrothermal reactor and held at 180℃ for 4.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold.
[0059] The microstructure of the inorganic bone cement bone tissue engineering scaffold was observed after curing at 80℃ for 5.0 hours, holding at 180℃ for 2.0 hours, and hydrothermally heating at 180℃ for 4.0 hours. The results are as follows: Figure 5As shown in the figure, the inorganic bone cement (calcium silicate bone cement) powder particles are bonded together by the calcium silicate gel fibers formed after hydration. Figure 5 a) is the fundamental reason for its strength formation. Although inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffolds are cured at 80℃ for 5.0 hours ( Figure 5 a) Incubate at 180℃ for 2.0 hours ( Figure 5 b) 180℃ hydrothermal for 4.0 hours ( Figure 5 c) Multiple treatments, especially heating to 180℃ and holding for 2.0 hours to initially remove the inner mold (thermoplastic polymer), did not cause complete dehydration or structural changes to the hydration products (calcium hydroxide and hydrated calcium silicate gel) inside the inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold due to the moderate temperature and short time. After undergoing multiple temperature treatments, the internal microstructure and composition of the inorganic bone cement bone tissue engineering scaffold did not change significantly. Therefore, this method not only demonstrates stability in size and macrostructure but also strong stability in the internal microstructure of the inorganic bone cement bone tissue engineering scaffold.
[0060] Example 6:
[0061] Using polylactic acid (PLA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) printer. The outer mold dimensions were Φ28×30mm, the inner mold gap was 1.5×1.5×1.5mm, and the filament width was 1.0mm. Dicalcium silicate was selected as the inorganic bone cement (calcium silicate bone cement) powder, and water was used as the curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.35ml / g and injected into the 3D printing mold. After curing at 80℃ for 5.0 hours, it was placed in a 180℃ oven and held for 1.0 hour. Then, it was placed in a hydrothermal reactor and held at 170℃ for 4.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D printed inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffold. Figure 6 a) The support is cylindrical, from the top surface ( Figure 6 b) and side ( Figure 6 c) Its structure is clearly visible. The cross-sectional dimensions of the inorganic bone cement bone tissue engineering scaffold are 1.5 × 1.5 mm, with a gap of 1.0 mm. The channel structure on the side of the cylinder is complete from the central axis (CL) to the edge, without any blockage. Combined with the above embodiments, it shows that this method can construct inorganic bone cement bone tissue engineering scaffolds of different sizes, shapes, and internal channel structures.
[0062] Example 7:
[0063] Using polyvinyl alcohol (PVA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) 3D printer. One outer mold measures 18×28×20mm, with an inner mold gap of 1.5×1.5×1.5mm and a filament width of 2.0mm. The second outer mold measures 20×34×18mm, with an inner Φ7.2mm cylinder and an inner hexagon with a side length of 2.0mm. Tricalcium silicate was selected as the inorganic bone cement (calcium silicate bone cement) powder, and water was used as the curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.30ml / g and injected into the 3D printing mold. After curing at 80℃ for 4.0 hours, the mold was placed in a 190℃ oven and held for 1.0 hour. The sample was then placed in a hydrothermal reactor and kept at 180°C for 4.0 hours. After removal, it was dried at 60°C for 2.0 hours to obtain two types of 3D-printed inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffolds. Figure 7 a) and b), the upper surface structure of the support is as follows Figure 7 As shown in c and d, this method can be used to construct inorganic bone cement bone tissue engineering scaffolds with more complex structures as needed.
[0064] Example 8:
[0065] Using polylactic acid (PLA) filament (Φ1.75mm) as consumables, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold were printed using a fused deposition modeling (FDM) 3D printer. The outer mold was 20×20×20mm in size. Tricalcium silicate was selected as the inorganic bone cement (calcium silicate bone cement) powder, and water was used as the curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.25ml / g and then injected into the 3D printing mold. After curing at 80℃ for 4.0 hours, the mold was placed in a 190℃ oven and held for 1.0 hour. The samples were then placed in a hydrothermal reactor and kept at 180℃ for 4.0 hours. After removal, they were dried at 60℃ for 2.0 hours to obtain 3D-printed inorganic bone cement (calcium silicate bone cement) bone tissue engineering scaffolds (as shown in Table 1). Six samples were tested for compressive strength using a mechanical testing machine. The results showed that the scaffold with a porosity of 50% had a strength of 26±3 MPa, which meets the support requirements in orthopedic clinical applications, and the scaffold has good mechanical properties. Table 1 also shows that the strength and porosity of the scaffold can be adjusted by designing the scaffold structure to meet application requirements.
[0066] Table 1. Compressive strength and porosity of supports of different sizes
[0067] 1 20×20×20mm 1.5×1.5×1.5mm 1.0mm 31±4MPa 40% 2 20×20×20mm 1.8×1.8×1.8 mm 0.7mm 44±3MPa 14% 3 20×20×20mm 2.0×2.0×2.0 mm 2.0mm 26±3MPa 50%
[0068] Example 9:
[0069] Using polyvinyl alcohol (PVA) filament (Φ1.75mm) as consumable, an inner and outer mold for an inorganic bone cement bone tissue engineering scaffold was printed using a fused deposition modeling (FDM) 3D printer. The outer mold dimensions were Φ24mm × 30mm, the inner mold gap was 1.5 × 1.5 × 1.5mm, and the filament width was 0.5mm. Tricalcium phosphate and amorphous calcium phosphate were selected as inorganic bone cement (calcium phosphate bone cement) powders, and water was used as the inorganic bone cement curing liquid. The powder and water were mixed at a liquid / solid ratio of 0.50ml / g and injected into the 3D printing mold. After curing at 80℃ for 5.0 hours, it was placed in a 180℃ oven and held for 3.0 hours. Then, it was placed in a hydrothermal reactor and held at 200℃ for 4.0 hours. After removal, it was dried at 60℃ for 2.0 hours to obtain the 3D-printed inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold, which was then implanted into experimental animal bone tissue. The histological morphology photographs are shown below. Figure 8 As shown. Three weeks after implantation ( Figure 8 a) The inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold is filled with bone tissue both outside and inside the pores (white arrows). As the inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold degrades, the pores enlarge, making room for cell and tissue ingrowth. Six weeks after implantation ( Figure 8 b) Further degradation of the inorganic bone cement (calcium phosphate bone cement) bone tissue engineering scaffold was found, with larger pores and a significant increase in osteogenic capacity, indicating that the inorganic bone cement bone tissue engineering scaffold has excellent osteogenic properties.
Claims
1. A method for preparing a 3D-printed inorganic bone cement bone tissue engineering scaffold, characterized in that, Includes the following steps: (1) On the fused deposition modeling 3D printer platform, using thermoplastic polymer materials as raw materials, print the inner mold and outer mold of inorganic bone cement bone tissue engineering scaffold; (2) The mixing liquid is mixed with inorganic bone cement powder to form a uniform inorganic bone cement slurry, which is then injected into a bone tissue engineering scaffold mold for curing. (3) After curing, first remove the outer mold, and then use the hot melt method to initially remove the inner mold; (4) Then use the hydrothermal method to thoroughly remove the remaining inner mold; (5) After removal, clean and dry to obtain a 3D printed inorganic bone cement bone tissue engineering scaffold; The thermoplastic polymer material is one or any combination of polylactic acid (PLA), polyethylene (PE), and polyvinyl alcohol (PVA); The inorganic bone cement is classified into one or any combination of calcium phosphate bone cement, calcium silicate bone cement, and magnesium phosphate bone cement; the inorganic bone cement consists of powder and curing liquid; the inorganic bone cement powder is one or any combination of tricalcium phosphate, tetracalcium phosphate, amorphous calcium phosphate, trimagnesium phosphate, magnesium hydrogen phosphate, magnesium oxide, tricalcium silicate, dicalcium silicate, and alkaline activated nano-silica self-curing powder; the mixing liquid is one or any combination of water, sodium chloride aqueous solution, calcium chloride aqueous solution, and magnesium chloride aqueous solution; the liquid / solid ratio is 0.20~0.60 mL / g; the curing temperature is 40~80℃, and the curing time is 1.0~6.0 hours; The inorganic bone cement bone tissue engineering scaffold mold is divided into an inner mold and an outer mold. The inner mold is the internal channel structure of the inorganic bone cement bone tissue engineering scaffold, and the outer mold is the outer surface mold of the inorganic bone cement bone tissue engineering scaffold, and is provided with an injection port for bone cement slurry. The initial removal of the inner mold using the hot-melt method is carried out at a temperature of 150~200℃ for 0.5~4.0 hours; the complete removal of the residual inner mold using the hydrothermal method is carried out at a temperature of 140~220℃ for 1.0~8.0 hours.
2. The method for preparing a 3D-printed inorganic bone cement bone tissue engineering scaffold according to claim 1, characterized in that: The cleaning solution is water, and the drying temperature is 40~80℃, with a drying time of 1.0~4.0 hours.
3. The method for preparing a 3D-printed inorganic bone cement bone tissue engineering scaffold according to claim 1, characterized in that: The 3D-printed inorganic bone cement bone tissue engineering scaffold has an internal gap greater than 0.2 mm and an internal column width of not less than 0.5 mm.
4. The method for preparing a 3D-printed inorganic bone cement bone tissue engineering scaffold according to claim 1, characterized in that, Includes the following steps: (1) Design the inner and outer molds of the inorganic bone cement bone tissue engineering scaffold as needed; (2) On the fused deposition modeling 3D printer platform, using thermoplastic polymer materials as raw materials, print the inner mold and outer mold of inorganic bone cement bone tissue engineering scaffold; (3) Mix the mixing liquid with inorganic bone cement powder at a liquid / solid ratio of 0.20~0.60 mL / g to form a uniform inorganic bone cement slurry. Inject the inorganic bone cement slurry into the bone tissue engineering scaffold mold and cure it rapidly at 40~80℃. (4) After curing for 1.0 to 6.0 hours, first remove the outer mold, then place it in an oven at 150 to 200°C and keep it warm for 0.5 to 4.0 hours to initially remove the inner mold; (5) The inorganic bone cement bone tissue engineering scaffold with part of the inner mold removed is placed in a hydrothermal reactor and reacted at 140~220℃ for 1.0~8.0 hours to completely remove the inner mold. After removal, it is cleaned and dried at 40~80℃ for 1.0~4.0 hours to obtain the 3D printed inorganic bone cement bone tissue engineering scaffold.
5. A 3D-printed inorganic bone cement bone tissue engineering scaffold prepared according to any one of claims 1-4.
Citation Information
Patent Citations
Porous calcium phosphate / natural polymer composite scaffold, preparation method and application thereof
CN108478879A
A piezoelectric nozzle for 3D printing of inorganic bone cement
CN112720779B
Controllable porous calcium phosphate scaffold and preparation method thereof
CN113233887A
Investment casting method
US3996991A